Assessment of Nugget Size of Spot Weld using Neutron Radiography - Triyono Triyono; Jamasri Jamasri; M.N. Ilman; R. Soekrisno; Sutiarso Sutiarso (PPIKSN-BATAN, 2011)
Resistance spot welding (RSW) has been widely used for many years in the fabrication of car body structures, mainly due to the cost and time considerations. The weld quality as well as the nugget size is an issue in various manufacturing and processes due to the strong link between the weld quality and safety. It has led to the development of various destructive and non-destructive tests for spot welding such as peel testing, ultrasonic inspections, digital shearography, and infrared thermography. However, such methods cannot show spot weld nugget visually and the results are very operator’s skill dependent. The present work proposes a method to visualize the nugget size of spot welds using neutron radiography. Water, oil and various concentrations of gadolinium oxide-alcohol mixture were evaluated as a contrast media to obtain the best quality of radiography. Results show that mixture of 5 g gadolinium oxide (Gd2O3) in 25 ml alcohol produces the best contrast. It provides the possibility to visualize the shape and size of the nugget spot weld. Furthermore, it can discriminate between nugget and corona bond. The result of neutron radiography evaluation shows reasonable agreement with that of destructive test. Received: 13 October 2010; Revised: 25 August 2011; Accepted 26 August 2011